Utilization of Quizizz-Based Digital Media in Islamic Religious Education Learning at SMKN 1 Bandar Lampung - Alifia Nuri Anggraini; Meriyati; Fitriani (IQRO: Journal of Islamic Education, 2026)
The use of Quizizz-based digital media in Islamic Religious Education (IRE) instruction at SMKN 1 Bandar Lampung aims to enhance student motivation, participation, and engagement in the learning process. This study employs a qualitative method with a field study approach. Data were collected through direct observation and in-depth interviews with key informants, consisting of PAI subject teachers and students from class X TJKT 3 (Computer Networking and Telecommunications Technology). The selection of these subjects was based on the students' vocational background, which involves high digital literacy, thereby minimizing technical barriers. Key findings indicate that the use of Quizizz transformed the PAI learning paradigm from one previously focused on rote memorization into a more interactive approach through gamification elements. Features such as leaderboards, timers, and instant feedback were proven to motivate students to participate actively and encourage self-directed learning. Additionally, the automatic reporting feature makes it easier for teachers to evaluate learning outcomes efficiently. Technical challenges, such as unstable internet connections, were addressed through creative solutions such as using tethering and group work systems. Based on these findings, it is recommended that the use of Quizizz be combined with project-based learning strategies to create a more effective and inclusive learning environment.